A constitutive model for the tensile behaviour of TWIP steels: Composition and temperature dependencies. (15th January 2016) - Kang, Jee-Hyun; Ingendahl, Tobias; Bleck, Wolfgang
Abstract: The tensile behaviour of three TWIP steels at 23 °C and 110 °C is interpreted by employing a one parameter constitutive model which predicts the dislocation density evolution via the approach suggested by Kocks and Mecking. The model parameters are critically reassessed based on previous studies. The composition and temperature dependencies of the shear modulus are calculated by taking magnetic ordering into account. Twinning kinetics is described as a function of the normalised stacking fault energy. The dynamic recovery rate is predicted by considering cross slip to be responsible for dynamic recovery. It is clear that higher dislocation densities are achieved at 23 °C compared to 110 °C for all alloys owing to the enhanced mechanical twinning and suppressed dynamic recovery. The shear modulus anomaly due to magnetic ordering can result in lower temperature dependency of the flow stress than that of the dislocation density depending on the composition. Graphical abstract: Highlights: Dislocation density based constitutive models for TWIP steels are reviewed. A constitutive model is employed to interpret tensile behaviour of TWIP steels. Model parameters are systematically related to temperature and alloy composition. Twinning and cross slip are significant to predict dislocation density evolution. Shear modulus anomaly should be considered to predict flow stress.